Growth and Characterization of Barium mixed Strontium tartrate single crystals - S. Mary Delphine1, R. Krishna Priya2, T.H. Freeda3, Abdul Wahab Almusallam4, M. Mary Freeda1*, (Recent Research in Science and Technology, 2010)
Single crystals of Barium mixed Strontium tartrate (SBT) were grown using silica gel as the growth medium. The crystalline nature of the grown crystal was confirmed using powder X-ray diffraction techniques. The functional groups present in the crystals were identified using Fourier Transform Infrared spectral analysis. Mechanical strength of the grown crystals was analyzed by Vicker’s microhardness test.